2007
DOI: 10.1111/j.1365-2249.2006.03303.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CD4+CD25+ regulatory T cells exacerbates sodium iodide-induced experimental autoimmune thyroiditis in human leucocyte antigen DR3 (DRB1*0301) transgenic class II-knock-out non-obese diabetic mice

Abstract: Both genetic and environmental factors contribute to autoimmune disease development. Previously, we evaluated genetic factors in a humanized mouse model of Hashimoto's thyroiditis (HT) by immunizing human leucocyte antigen DR3 (HLA-DR3) and HLA-DQ8 transgenic class II-knock-out non-obese diabetic (NOD) mice. DR3+ mice were susceptible to experimental autoimmune thyroiditis (EAT) induction by both mouse thyroglobulin (mTg) and human (h) Tg, while DQ8+ mice were weakly susceptible only to hTg. As one environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 54 publications
(100 reference statements)
0
12
0
1
Order By: Relevance
“…This is presumably due to extremely low frequency of Tg-specific T eff in NOD-H2 h4 mice, although anti-Tg autoantibodies were readily detected as demonstrated above, but not due to a matter of antigenicity of Tg, although iodination of Tg has been reported to enhance its antigenicity (30). Fynn et al (31) also observed no T cell proliferation to Tg in DR3 transgenic class II-knockout NOD mice. Furthermore, similar data have been reported in NOD mice; detection of insulin-specific T cell response has been reported to be difficult in the mice, despite clear elevation of antiinsulin autoantibodies in their sera (32).…”
Section: Discussionmentioning
confidence: 73%
“…This is presumably due to extremely low frequency of Tg-specific T eff in NOD-H2 h4 mice, although anti-Tg autoantibodies were readily detected as demonstrated above, but not due to a matter of antigenicity of Tg, although iodination of Tg has been reported to enhance its antigenicity (30). Fynn et al (31) also observed no T cell proliferation to Tg in DR3 transgenic class II-knockout NOD mice. Furthermore, similar data have been reported in NOD mice; detection of insulin-specific T cell response has been reported to be difficult in the mice, despite clear elevation of antiinsulin autoantibodies in their sera (32).…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, as we predicted, the timing of depletion prior to increased dietary iodide appears to be a critical factor for CD4 þ CD25 þ Treg to exert their suppressor function. While we nearly completed the present study, Flynn et al [27] published an article showing exacerbation of iodide-induced thyroiditis in a different mice (human DR3 transgenic class II-knock out NOD mice) by injecting anti-CD25 antibody 2 and 1.5 weeks before starting NaI water (the shorter time lapse than that in the study of Yu et al [18]). …”
Section: Discussionmentioning
confidence: 79%
“…Tai patvirtina nuomonę, kad HLA-DRB1 polimorfizmas lemia jautrumą autoimuniniam tiroiditui. Be to, šio gyvūno modelio metu pastebėta, kad padidintas jodo kiekis maiste paspartina skydliaukės ligos susiformavimą, o CD4+, CD25+ T ląstelių stygius sunkina jodo sukeltą tiroidito eigą (10). Dar vieno naujo tyrimo metu tyrėjai pastebėjo, kad nekrotizavusios skydliaukės folikulų epitelinės ląstelės gali sukelti dendritinių ląstelių subrendimą in vitro, po to šias dendritines ląsteles sušvirkštus atgal autologinėms pelėms, sukeliamas eksperimentinis autoimuninis tiroiditas, kurio metu būna limfocitinė skydliaukės infiltracija ir nustatoma tiroglobulinui specifinių imunoglobulinų G (11).…”
Section: Eksperimentinis Autoimuninis Tiroiditasunclassified